EDUCATIONAL ACTION FOR STANDARDIZATION IN THE MANAGEMENT OF HICKMAN CATHETERS® - Mitzy Tannia Reichembach Danski; Sandra Regina da Silva; Letícia Pontes; Edivane Pedrolo (Universidade Federal do Paraná, 2018)
Objective: to enable the nursing team of a hematopoietic stem cell transplantation service to manage Hickman® catheters. Method: descriptive and quantitative research. Data collection took place between January and March 2017, in a public hospital in the South of Brazil, using questionnaires that were analyzed through descriptive statistics. Results: Forty-four participants were enrolled. Of the issues addressed, the ones with better results after the guidelines were: definition of a short-term central venous catheter (79.55% for 93.18% of correct answers); material and position of the catheter (75% to 88.64%); characteristics of the catheter (54.55% to 65.91%); immediate procedures after catheter insertion (2.27% to 18.18%); flushing, positive pressure and syringe-induced reflux (72.73% to 97.73%); catheter lock (84.09% to 97.73%); and priming volume (22.73% to 54.55%). Conclusion: the educational process developed allowed the instrumentalization of professionals to a more homogenous knowledge in the management of Hickman® catheters.